Finger sucking callus as useful indicator for malocclusion in young children. Issue 3 (December 2016) - Oyamada, Yu; Ikeuchi, Tomoko; Arakaki, Makiko; Hino, Ryoko; Ono, Mariko; Kobayashi, Mayu; Yamaguchi, Satoko; Saito, Kan; Yamada, Aya; Fukumoto, Satoshi
Abstract: Purpose: Finger sucking is the most commonly observed habit in children. However, a prolonged sucking habit may have negative effects on dentition and occlusal development, including maxillary protrusion, anterior open bite, and posterior cross-bite. For treatment of malocclusion, early detection is important, especially in children, though it is difficult to exam oral habits using typical dental examination methods. In this study, we report the relationship between a callus on the sucking finger and malocclusion. Methods: While performing dental examinations, we checked the fingers of 719 children (0–6 years old) who were attending 10 different kindergartens in Sendai City, Japan, in 2009 to determine the presence of a sucking callus formed by a finger sucking habit. Results: The peak ratios of children with a sucking callus and malocclusion was at the age of 2 years (13.6% and 11.0%, respectively), and then decreased with age. Maxillary protrusion was detected in 42.9%, 56.2%, 42.9%, and 37.5% of the children with a sucking callus at the age of 1, 2, 3, and 4 years old, respectively. In those with maxillary protrusion, a sucking callus was detected in 42.9%, 75%, 75%, and 60%, respectively. Conclusion: We concluded that the presence of a sucking callus is a useful indicator for malocclusion caused by an oral habit.